Comparing the efficacy of different types of exercise for the treatment and prevention of depression in youths: a systematic review and network meta-analysis - Zhang, Yihan; Li, Geng; Liu, Chengzhen; Guan, Jinliang; Zhang, Yuantong; Shi, Zifu (Frontiers in Psychiatry, 2023)
Purpose Depression disorder is the most commonly diagnosed type of mental illness among youths. Although a plethora of evidence suggests a positive relationship between exercise and lower levels of depression in youths, the findings regarding the variation in magnitude of this relationship are inconclusive with respect to the preventive and therapeutic effects of different types of exercise. This network meta-analysis aimed to determine the best type of exercise for the treatment and prevention of depression in youths. Methods A comprehensive search of databases, including PubMed, EMBASE, The Cochrane Library, Web of Science, PsychINFO, ProQuest, Wanfang, and CNKI, was conducted to identify relevant research on exercise interventions for depression in youth populations. The risk of bias in the included studies was evaluated using Cochrane Review Manager 5.4 according to the Cochrane Handbook 5.1.0 Methodological Quality Evaluation Criteria. The network meta-analysis was performed using STATA 15.1 to calculate the standardized mean difference (SMD) of all concerned outcomes. The node-splitting method was used to test the local inconsistency of the network meta-analysis. Funnel plots were used to evaluate the potential impact of bias in this study. Result Utilizing data extracted from 58 studies (10 countries, 4,887 participants), we found that for depressed youths, exercise is significantly better than usual care in reducing anxiety (SMD = −0.98, 95% CI [-1.50, −0.45]). For non-depressed youths, exercise is significantly better than usual care in reducing anxiety (SMD = −0.47, 95% CI [ −0.66, −0.29]). In the treatment of depression, resistance exercise (SMD = −1.30, 95% CI [ −1.96, −0.64]), aerobic exercise (SMD = −0.83, 95% CI [-1.10 −0.72]), mixed exercise (SMD = −0.67, 95% CI [−0.99, −0.35]), and mind-body exercise (SMD = −0.61, 95% CI [−0.84, −0.38]) all showed significant efficacy over usual care. For the prevention of depression, resistance exercise (SMD = −1.18, 95% CI [-1.65, −0.71]), aerobic exercise (SMD = −0.72, 95% CI [−0.98, −0.47]), mind-body exercise (SMD = −0.59, 95% CI [-0.93, −0.26]), and mixed exercise (SMD = −1.06, 95% CI [−1.37 to −0.75]) were all significantly effective compared to usual care. According to the test of the surface under the cumulative ranking score (SUCRA), the ranking of exercises for the treatment of depression in depressed youths is as follows: resistance exercise (94.9%) > aerobic exercise (75.1%) > mixed exercise (43.8%) > mind-body exercise (36.2%) > usual care (0%). For the prevention of depression in non-depressed youths, resistance exercise (90.3%) > mixed exercise (81.6%) > aerobic exercise (45.5%) > mind-body exercise (32.6%) > usual care (0%). Resistance exercise thus had the best comprehensive effect on both the treatment and prevention of depression in youths (clusterank value = 1914.04). Subgroup analyses show that a frequency of 3–4 times per week, a duration of 30–60 min, and a length of more than 6 weeks were found to be the most effective interventions for depression (P > 0.001). Conclusion This study provides compelling evidence that exercise is a viable intervention for improving depression and anxiety in young individuals. In addition, the study emphasizes the importance of selecting the appropriate type of exercise to optimize treatment and prevention. Specifically, the results suggest that resistance exercise, performed 3–4 times per week, with sessions lasting 30–60 min and a length of more than 6 weeks, yields optimal results for the treatment and prevention of depression in young individuals. These findings have significant implications for clinical practice, particularly given the challenges associated with implementing effective interventions and the economic burden of treating and preventing depression in young people. However, it is worth noting that additional head-to-head studies are necessary to confirm these findings and strengthen the evidence base. Nevertheless, this study provides valuable insights into the role of exercise as a potential treatment and preventative measure for depression in young people. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=374154, identifier: 374154.